LOCAL GOVERNMENT POLICY IN HANDLING CORONAVIRUS (COVID-19) PANDEMIC IN SURABAYA (Universitas 17 Agustus 1945 Surabaya, 2021)
Exactly on March 16, 2020, this virus has begun to enter the Surabaya area. This study wants to see about the Covid-19 pandemic in Indonesia. There are two problems investigated in this study. First, regarding kebijaka n issued by local governments in addressing the pandemic Covid-19, especially in the city of Surabaya . Second, researchers wanted to see the impact of their policies issued by the city of Surabaya in the face of a pandemic Covid-1 9 against the public economy. The theory used to analyze this problem is Merilee S. Grindle's theory of public policy implementation. The research method is descriptive qualitative and the type of research is a case study.From the data analysis, it can be seen that the first finding, there are several policies issued by the Surabaya city government in dealing with the Covid-19 pandemic, namely, 1) Surabaya Mayor's Circular to Increase Awareness of Covid-19 in Surabaya. 2) Population Mobility Control Protocol Based on the Circular Letter of the Mayor of Surabaya. 3) Surabaya Mayor Regulation Number 16 of 2020 concerning Guidelines for Large-Scale Social Restrictions in Handling Covid-19 in the City of Surabaya. 4) Decree of the Mayor of Surabaya regarding the Task Force for the Acceleration of Handling Covid-19 in the city of Surabaya. 5) Surabaya Mayor Regulation Number 28 of 2020 concerning Guidelines for the New Normal Order in the Conditions of the Covid-19 Pandemic.